1997
DOI: 10.1103/physrevb.55.r8685
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of Josephson plasma and vortex oscillation modes inBi2Sr2

Abstract: The Josephson plasma resonance of Bi 2 Sr 2 CaCu 2 O 8ϩ␦ in parallel magnetic fields has been measured by angular alignment with ϳ0.02 degree precision to reveal the phase collective modes in the Josephson vortex lattice. When the angle between the field and the CuO 2 plane is tilted from the c axis, the resonance field scales as H sin in the range տ4°. At lower angles, the resonance field shows anomalous decreases with decreasing . A disappearance of the resonance has been unexpectedly found for angles within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 12 publications
1
39
2
Order By: Relevance
“…In Bi-2212, there have been microwave resonance measurements under parallel applied magnetic fields [14,15,16], and resonance peaks have been observed in microwave absorption spectra. However, in the microwave study, it is not possible to discuss the origin of the observed modes quantitatively.…”
mentioning
confidence: 99%
“…In Bi-2212, there have been microwave resonance measurements under parallel applied magnetic fields [14,15,16], and resonance peaks have been observed in microwave absorption spectra. However, in the microwave study, it is not possible to discuss the origin of the observed modes quantitatively.…”
mentioning
confidence: 99%
“…We now seek a uniform, in the z-direction, solution of Eq. (12). Normalizing the coordi-nate x to λ c and time t to 1/ω J , we can rewrite Eq.…”
Section: B Theory Of Superradiance In the Resistive Modementioning
confidence: 99%
“…As with other resonance methods, the Josephson plasma resonance is a sensitive and convenient tool for the study of the material properties [11][12][13][40][41][42][43][44][45][46]. Evidently, the JPR gives direct information about the Josephson coupling of the superconducting layers.…”
Section: Josephson Plasma Resonancementioning
confidence: 99%
See 1 more Smart Citation
“…The Josephson plasma resonance (JPR) observed in the microwave absorption [1], and in optical reflection [2][3][4][5] and transmission measurements [6,7], has proven to be a powerful method to study the properties of highly anisotropic layered superconductors, such as vortex phases [1,8]. In particular, the spatial dispersion of the JPR, ω p (k, k z ), parallel (k) and perpendicular (k z ) of the superconducting layers reflects the inductive coupling of junctions due to intralayer currents and the charge coupling due to the variations of the electrochemical potential on the layers, respectively.…”
mentioning
confidence: 99%